Pengaruh Pengetahuan, Kontrol Diri terhadap Perilaku Seksual Pranikah di Kalangan Remaja SMK di Surabaya - Nita Istiqomah; Hari Basuki Notobroto (Universitas Airlangga, 2016)
The premarital sexual behavior adolescent has become a social problem in the community. Free sexual behavior are various ranging from feeling of attraction to the opposite sex, dating, kissing, holding partsof the body that are sensitive until sexual intercourse. Two factors that can infl uence sexual behavior are knowledge and self control. Adolescent who have high knowledge and self control tend to not perform sexual behavior. The purpose of this study was to analyze the effect of knowledge and premarital sexual behavior self control in adolescent of SMK in Surabaya. This study was performed using cross sectional study design. The study population was students of class XI SMK in Surabaya. Subjects were selected by proportional stratified random sampling. Sample was 83 students. Data analysis was performed using chi square test (α = 0.05). The results of this study were self-control influenced knowledge (p = 0.000; PR = 11.000), knowledge infl uenced premarital sexual behavior (p = 0.000; PR = 10.607) and self-control infl uenced premarital sexual behavior (p = 0.000; PR = 46.970). The conclusion of this research is variables knowledge and self-control infl uence premarital sexual behavior SMK in Surabaya increasing increase knowledge of adolescent in relation to premarital sexual behavior before marriage through counseling in Generation Program Plan (GENRE). Genre was can be a alternative solution to decrease premarital sexual behavior.